Cybersecurity training and healthcare: the AERAS approach - Frati, Fulvio; Darau, Georgiana; Salamanos, Nikos; Leonidou, Pantelitsa; Iordanou, Costas; Plachouris, Dimitris; Syrmas, Efstratios; Floros, Evangelos; Nikitakis, George; Spanoudakis, George; Kalais, Konstantinos; Tsichlaki, Stella; et al. (My University, 2024)
Cyber ranges have gained significant importance in cybersecurity training in recent years, and they are still playing a role of paramount importance, thanks to their ability to give trainees hands-on experience with real-world exercises. This paper presents the motivation and objective of the AERAS project, including a thorough analysis of data from ad hoc interviews and surveys specifically designed and administered for the project’s goals. AERAS aims to apply the cyber range concept to the critical healthcare sector. The AERAS platform will be a virtual cyberwarfare solution that will simulate the operation and effects of security controls and offer hands-on training on their development, assessment, use, and management.
Keywords: Cyber range training; Cybersecurity; Healthcare personnel training; Healthcare sector